IPAPM 2019
DOI: 10.36648/2471-982x.5.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the appearance of dural post-puncture headache in patients undergoing elective cesarean section.

Abstract: An epidemiological, observational, analytical and retrospective study of cases and controls was conducted with women undergoing elective cesarean section under spinal anesthesia at the Carlos Manuel de Céspedes Hospital in Bayamo, Granma province, from February 2013 to December 2015; with the objective of identifying the risk factors hypothetically related to the appearance of postpuncture dural headache in obstetric patients undergoing elective cesarean section.All the patients who gave their consent to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
3
1
1
Order By: Relevance
“…This study found that women who had 2, 3, and >3 puncture attempts were, respectively, 8, 28, and 20 times more likely to develop PSH as compared to those who had 1 attempt. This is consistent with a study done in Cuba [ 20 ] and the one done by Tarekegn et al [ 4 ] in Ethiopia. The number of puncture attempts is a reflection of the magnitude of damage that is caused, resulting in more sites from which CSF is lost; therefore, fewer attempts result in a lower incidence of PSH.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study found that women who had 2, 3, and >3 puncture attempts were, respectively, 8, 28, and 20 times more likely to develop PSH as compared to those who had 1 attempt. This is consistent with a study done in Cuba [ 20 ] and the one done by Tarekegn et al [ 4 ] in Ethiopia. The number of puncture attempts is a reflection of the magnitude of damage that is caused, resulting in more sites from which CSF is lost; therefore, fewer attempts result in a lower incidence of PSH.…”
Section: Discussionsupporting
confidence: 94%
“…This study found that participants with prior chronic headache were 3 times more likely to develop PSH ( p =0.006), compared to those who reported no history of headache. This is consistent with the study done by Jabbari et al [ 13 ] in his review of articles and the one done by Frias Carrazana et al in Cuba [ 20 ]. The precise reason for this is unknown, but it is speculated that there could be some unique physiologic and neurologic transmitters that could explain the risk.…”
Section: Discussionsupporting
confidence: 93%
“…The effect of normal BMI, multiple attempts, and using needle size less than and equal to 22 gauge was in line with studies done in Japan [ 19 ], Ethiopia and Jordan [ 15 , 16 ] and, Cuba [ 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…The pooled prevalence of PDPH in this meta-analysis was higher than studies done in Jordan by Khraise et al, 2017 with a prevalence of 6% [ 16 ], Nigeria by Mohammed et al, 2017 with a prevalence of 15.8% [ 18 ], Japan by Makito et al, 2020 with a prevalence of 1.16% [ 19 ] and turkey by Pirbudak et al, 2019 with a prevalence of 10.8% [ 22 ]. Our result is lower than studies done in Ethiopia by Tarekegn et al, 2017 with a prevalence of 42.6% [ 15 ], in Mulago by Nambooze et al, 2019 with a prevalence of 48.8% [ 17 ], in Cuba by Carrazana et al, 2018 with a prevalence of 33.3% [ 20 ] and in Turkey by Uluer et al, 2019 with a prevalence of 30% [ 21 ]. The discrepancy might be due to the variation in sociodemographic characteristics across studies, clinical setup differences, and study design.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation